The Role of Information Technology in Improving Information Systems: A Comprehensive Review - Prayitno, Andi; Sinosi, Sayidah Maryam; Mediaty, Mediaty; Damayanti, Ratna Ayu (INVOICE : JURNAL ILMU AKUNTANSI, 2025)
This study explores the strategic significance of Information Technology (IT) in enhancing organizational competitiveness, particularly through its impact on employee productivity, decision-making processes, and business process efficiency. The rapid evolution of digital technologies has compelled organizations to integrate IT as a core component of their operational and strategic frameworks. To examine this relationship systematically, the study employs a Systematic Literature Review (SLR) method, analyzing 15 peer-reviewed articles published between 2018 and 2023. Articles were selected based on inclusion criteria such as relevance to IT adoption, methodological rigor, and empirical depth. The review identifies key factors that influence successful IT integration, including top management support, user training, trust in system reliability, and perceived usefulness. Notably, 80% of the reviewed studies demonstrate a strong positive correlation between IT integration and employee performance, especially in enhancing data accessibility, enabling real-time collaboration, and supporting informed decision-making. Furthermore, the findings reveal that effective IT usage contributes not only to financial performance but also to non-financial outcomes such as employee satisfaction and organizational adaptability. These results underscore the strategic value of IT in fostering both operational excellence and workforce empowerment. The study offers practical recommendations for managers and policymakers to enhance IT adoption strategies and align technological initiatives with organizational goals.